Association of Aldosterone with Mortality in the General Population - Then, Cornelia; Herder, Christian; Heier, Margit; Meisinger, Christa; Koenig, Wolfgang; Rathmann, Wolfgang; Sujana, Chaterina; Roden, Michael; Bidlingmaier, Martin; Seissler, Jochen; Thorand, Barbara; Peters, Annette; Reincke, Martin (Experimental and Clinical Endocrinology & Diabetes, 2023)
Introduction Aldosterone excess is linked to cardiovascular events and mortality as well as to low-grade inflammation in the context of metabolic diseases. Whether mildly elevated aldosterone levels in the general population promote cardiovascular risk is still under debate. We analyzed the association of plasma aldosterone concentrations with incident cardiovascular events, cardiovascular and all-cause mortality as well as with biomarkers of subclinical inflammation in the population-based KORA F4 study.Methods Plasma aldosterone concentrations were measured with an in-house immunoflurometric assay. The analyses included 2935 participants (n=1076 for selected biomarkers of subclinical inflammation) with a median follow-up of 8.7 (8.2; 9.1) years. The associations were estimated using Cox proportional hazard and linear regression models adjusted for renin, sex, age, body mass index, arterial hypertension, diabetes, estimated glomerular filtration rate, low- and high-density lipoprotein cholesterol, physical activity, smoking, use of angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, beta-blockers, diuretics and calcium channel blockers.Results Aldosterone was significantly associated with all-cause mortality (hazard ratio per standard deviation increase: 1.20; 95% confidence interval 1.04–1.37), but not with cardiovascular mortality, incident cardiovascular events, or with biomarkers of subclinical inflammation.Conclusions Aldosterone was associated with all-cause mortality in the population-based KORA F4 study, but the previously described associations of excess aldosterone with cardiovascular complications and biomarkers of subclinical inflammation could not be shown.
Keywords: renin; stroke; myocardial infarction; general population